2016
DOI: 10.1021/acs.nanolett.6b00428
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Universal Temperature Scaling in Self-Heated Percolating Networks

Abstract: During routine operation, electrically percolating nanocomposites are subjected to high voltages, leading to spatially heterogeneous current distribution. The heterogeneity implies localized self-heating that may (self-consistently) reroute the percolation pathways and even irreversibly damage the material. In the absence of experiments that can spatially resolve the current distribution and a nonlinear percolation model suitable to interpret them, one relies on empirical rules and safety factors to engineer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…This induces the presence of hotspots close to the percolation threshold that disappear progressively at higher network density. Also recently, thermoreflectance imaging has been successfully used to detect the presence of hotspots and study the local degradation mechanisms in either pristine AgNW networks, 16 hybrid graphene−AgNW networks, 17 or polymer assisted-templated Ag networks. 18 All these studies provided interesting information regarding current distribution in AgNW networks at the microscale.…”
mentioning
confidence: 99%
“…This induces the presence of hotspots close to the percolation threshold that disappear progressively at higher network density. Also recently, thermoreflectance imaging has been successfully used to detect the presence of hotspots and study the local degradation mechanisms in either pristine AgNW networks, 16 hybrid graphene−AgNW networks, 17 or polymer assisted-templated Ag networks. 18 All these studies provided interesting information regarding current distribution in AgNW networks at the microscale.…”
mentioning
confidence: 99%
“…LiT can be compared to the thermo-reflectance (TR) imaging technique, which has also recently proven efficient for detecting hot spots in percolating nanocomposites. 49 Here, we have also evaluated the effect of electrode geometry and the nanowire dimensions on the quantized percolation phenomenon. Finally, we demonstrate for the first time that the breakdown of the networks can also happen in a quantized manner.…”
mentioning
confidence: 99%
“…In a more general way, such technique can be used to map the heat generated locally by Joule effect across the network to reveal how electric current is distributed through the percolating pathways. LiT can be compared to the thermo-reflectance (TR) imaging technique, which has also recently proven efficient for detecting hot spots in percolating nanocomposites . Here, we have also evaluated the effect of electrode geometry and the nanowire dimensions on the quantized percolation phenomenon.…”
mentioning
confidence: 99%
“…Das et al investigated scaling in self‐heated percolating networks and concluded that hotspot clustering appears to be a mechanism analogous to crystallization physics. [ 89 ] The potential presence of hotspots will be discussed in this review, since their presence can lead to TH instability. In brief, the thermal stability of the TH can be limited to the TH itself (e.g., degradation of the conductive polymer or morphological instability of silver nanowires [ 90 ] ) or to the substrate as well.…”
Section: Principle Of Thsmentioning
confidence: 99%